STUDI KOMPERATIF ANTARA ABD. RACHMAN ASSEGAF DAN MUJAMIL QOMAR TENTANG PEMBELAJARAN PENDIDIKAN ISLAM MULTIDISIPLINER - Ramadhan, Rahmad; Robi’ah, Robi’ah (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This study aims to determine the thoughts of Abd. Rachman Assegaf and Mujamil Qomar on Islamic education learning, knowing the similarities and differences in Islamic education learning thoughts of the two figures. By using data collection techniques in the form of studying and collecting data through reading materials sourced from primary books and secondary books related to the two figures discussed. This research uses a qualitative descriptive approach, and the type of research used is library research, namely collecting data or scientific papers that aim at the object of research or collecting data that is literature. From the results of the research, it is concluded that the Islamic Education Learning Perspective of Abd. Rachman Assegaf is a multidisciplinary scientific approach, harmonizing and making a balance (tawazun) between God’s revelation and the findings of the human mind, where it will not result in reducing the role of God (secularization) or isolating humans so that they are alienated from themselves, society and their environment. Conversely, the concept of reintegration of multidisciplinary scientific epistemology will also be able to resolve conflicts between extreme secularism and negative fundamentalism from rigid and radical understandings. Meanwhile, according to Mujamil Qomar, multidisciplinary Islamic education learning is an Islamic learning activity carried out by involving other disciplines to participate in helping to solve problems together by using their respective approaches and methods autonomously and there is no intervention of one discipline against another. In another sense, the multidisciplinary approach positions all disciplines to stand alone and work using methods freely in contributing to problem solving